Insulin Secretory Status in Obese Female - Tasnim, Masuma; Akhter, Qazi Shamima; Akhter, Salma; lovely, Nasreen Sultana; Begum, Khadiza; Sinha, Susmita (Journal of Bangladesh Society of Physiologist, 2015)
Background: In obesity insulin hypersecretion is a key feature indicating the abnormal pancreatic beta cell function which is the fundamental defect in the development of NIDDM, hypertension and cardiovascular diseases. Objective: To assess the secretory status of insulin in adult obese female. Methods: The present study was a cross sectional analytical study and conducted in the Department of Physiology, Dhaka Medical College, Dhaka from July 2012 to June 2013. 50 obese female subjects of 20-40 years were included from Out-patient Department (Obesity clinic) of BIRDEM Hospital, Dhaka and by personal contact from different areas of Dhaka city. 50 age matched, healthy non-obese female subjects selected as controls . Fasting serum insulin level was measured by ELISA and fasting glucose level was measured by Glucose oxidase method. The insulin secretory status was calculated by HOMA-%B using HOMA software. For statistical analysis unpaired Students t test and Pearsons correlation coefficient (r) test were performed as applicable . Result: Mean fasting serum insulin and HOMA%B (P<0.001) were higher in the obese than that non obese. Fasting serum insulin level and HOMA%B showed significantly positive correlation with WHR. Conclusion: This study concludes that obese individual develops a state of insulin hypersecretion and hyperinsulinemia. DOI: http://dx.doi.org/10.3329/jbsp.v9i2.22800 Bangladesh Soc Physiol. 2014, December; 9(2): 72-77